Global Ionospheric Metal Ion Transport With SAMI3. Issue 14 (30th July 2019) - Huba, J. D.; Krall, J.; Drob, D.
Abstract: The first global simulation of metal ion dynamics in both the E and F regions is presented. The Naval Research Laboratory ionosphere/plasmasphere model SAMI3 has been upgraded to include the metal ions Mg + and Fe + with full ion transport (but not deposition or chemistry). The combination of the neutral wind and global electric field dramatically redistributes the metal ions in the ionosphere. High‐density layering can occur in the low to middle latitude, as well as the polar cap, E regions; this can be a significant factor in the development of sporadic E . Both the wind and electric field are important in the low‐ to middle‐latitude ionosphere, while the electric field is more important than the wind at high latitudes. Additionally, metal ions can be lifted to high altitudes ( ≳ 600 km) in the low‐ to middle‐latitude ionosphere. Key Points: The first global transport model of metal ions in the ionosphere is presented Metal ion layering occurs in the midlatitude and polar cap regions Metal ions can be lifted to altitudes up to 600 km in the midlatitude F region